Security Assessment and Testing Tools Information Repository - Mendes, Naaliel; Durães, João; Vieira, Marco; Madeira, Henrique (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2008: Anais do IX Workshop de Testes e Tolerância a FalhasDO - 10.5753/wtf.2008.23148, 2008)
This paper presents a repository for storing and comparing the characteristics of security assessment and testing tools. This repository supports information on the tools from different sources, ranging from specialized web sites and magazines to academic publications. This is in fact a powerful mean to share and disseminate information on security testing tools and to raise security issues awareness. It can also represent a very important information source for researchers and practitioners interested in exploring those tools. A working version of the repository is already online.